Pengaruh Bersyukur Terhadap Kesehatan Mental Mahasiswa PENS - Nathan; Erik (Nathiqiyyah, 2023)
Mental health issues among students have become an increasingly serious public health concern. According to data from the World Health Organization (WHO), one in five students experiences mental health disorders. One influencing factor on mental health is a lack of gratitude. Gratitude is defined as recognizing and appreciating everything in life, be it in thoughts, words, or actions. This research focuses on the influence of gratitude on the mental health of students at the Surabaya State Electronic Polytechnic (PENS). The study utilized a questionnaire distributed through Google Forms to gather data on students' perspectives regarding gratitude and its impact on mental health. The research findings indicate that the majority of PENS students have a relatively high level of well-being, although a significant number of students experience notable levels of stress and anxiety. Most respondents believe that gratitude plays a crucial role in maintaining their mental health. Data analysis reveals a significant positive correlation between gratitude, happiness levels, agreement on the importance of gratitude, and overall mental health. Awareness of the significance of gratitude also positively correlates with mental health, providing evidence that feelings of gratitude can reduce the risk of stress and depression among PENS students.